Geochemical classification of mafic plutonic rocks in the Häme and Pirkanmaa belts, SW Finland - Kotivuori, Antti (My University, 2023)
The Häme and Pirkanmaa belts are located in the Paleoproterozoic Svecofennian tectonic province in SW Finland. In this study geochemical results from 59 intrusive mafic and intermediate rock samples from the Häme and Pirkanmaa belts area are investigated with the purpose to (i) classify the mafic rocks and reveal the similarities, differences and patterns between the samples and between the Häme and Pirkanmaa belts, to (ii) compare results with the earlier investigations from the area and to (iii) try define the possible age of the samples, to (iv) find evidence on the occurrence of mafic rocks with origin in other than arc-type mafic magmas and to (v) further refine the picture we have on the mafic rocks of the Häme and Pirkanmaa belts. The samples were collected in 2017 and 2018 during the co-operative project of the Geological Survey of Finland (GTK) and the University of Turku. Most of the analyzed samples show Volcanic Arc Basalt (VAB) –type geochemical features, but several samples with Enriched Mid-Ocean-Ridge-Basalt (E-MORB) and Within Plate Basalt (WPB) –type features were encountered. Some of the samples are similar to the high-Nb and high-Mg gabbros and some are similar to the Uunimäki gabbro. The E-MORB affinity rocks and the tholeiitic VAB rocks with high Pb anomaly are more common in the Häme belt and the calc-alkaline VAB rocks with higher Rb contents in the Pirkanmaa belt area. The major and trace element bivariate diagrams of the Pirkanmaa belt samples suggest that the plagioclase composition could be closer to calcium feldspar endmember of the plagioclase feldspars series, whereas in the Häme belt plagioclase composition could be closer to sodium feldspar endmember and/or pyroxenes are more common. The samples from the southern parts of the Häme belt show contradicting geochemical features which suggest a more complex tectonic setting in comparison to samples from the northern parts of the belt. The analyzed samples represent multitudes of tectonic settings, but the formation of most of the samples is likely related to the early Svecofennian orogen cycle at c.1.90 – 1.86 Ga.
Keywords: geochemistry, Svecofennian orogeny, mafic magmatism